Proposta de ensino para a prática do Futebol no contexto da abordagem crítico-emancipatória - Lima, José Fábio de Albuquerque (2023)
School Physical Education has suffered over the years several influences from sports practices and performance. Soccer is one of the most practiced sports in Physical Education classes, but without many reflections and questions, and often without a clear methodological perspective and devoid of meanings for elementary school students. Therefore, the theme of that study was “Teaching proposal for the practice of football in the context of the critical-emancipatory approach.” The criticalemancipatory approach aims at forming a critical and emancipated subject, who has autonomy and conscience to understand the phenomena and contexts that permeate society and, for that, to plan an educational environment, where the student has the freedom to create, criticize and opine. In this way, the research aims to reflect, in addition to technical aspects, what football can provide for the development of the individual, providing him through this sport, to develop competences of autonomy, creativity, social interaction, objective competences, among others. others. The present study plans to develop a football teaching proposal based on the criticalemancipatory approach, in an 8th grade elementary school class, analyzing the teacher's challenges for the application of a critical-emancipatory teaching proposal, as well as, together with the students from the aforementioned class, experiencing sports at school, especially football throughout their school career. In addition, reflect and discuss this proposal, and the teaching-learning process. Thus, this study will be qualitative, descriptive, and exploratory in nature because it refers to the understanding of processes that occur in a given institution or community. Therefore, it is a qualitative case study, with participatory research, where there is interaction between the researcher and the subjects involved in the actions. Our research universe was the State school Professor Manuel João, located in the city of Grossos-RN, circumscribed in the 12th DIREC, linked to the secretary of education of the state of Rio Grande do Norte, where the students regularly enrolled in the 8 th year of elementary school. Data collection was carried out through the students' class diary, observing the activities developed during classes in the class and records in the researcher's diary, with records and notes. For the analysis of the data of this study we used the thematic modality of content analysis, where the information will be raised qualitatively, through the observation of the study participants. As challenges found in this study, we point to difficulty in the relationship of genders or mixed classes, students still resistant to sport spectacle and the school's relationship in a critical teaching perspective. As positive points, we highlight the participation of students and reflection on the teaching practice. The results showed us that it is possible to develop the practice of football at school with a critical-emancipatory sense, where students can give new meanings to their lived context, in addition to providing a reflection on our teaching practice.